An approach in creating positive emotion for children’s e-learning based on user interface design - Magrizef Gasah; Nurul Hidayah Mat Zain; Aslina Baharum (Institute of Advanced Engineering and Science, 2019)
This paper presents an approach in creating positive emotion for children’s e-learning using user interface design. The problems that this research aims to solve are the lack of children interest in school and early childhood school dropout. This research consists of three phases where each phase has its own research method. In this paper, the proposed research method aims to identify the user interface design that could trigger positive emotion and achieved using a qualitative method and quantitative method. The result shows a guideline for creating e-learning application that could help designer and developer to develop the application. Hopefully, the guideline of the positive emotion and the e-learning application could help the children more interested in school and learning in the future.